Apego y el perfil neurocognitivo en usuarios diagnosticados con trastorno del espectro autista de 1 a 5 años atendidos en el centro de integración sensorial para niños con autismo y desorden en el desarrollo (CISADDE IPS) en la ciudad de Barranquilla (2020)
Present investigation include concepts of attachment, Parenting guidelines, neurocognitive profile and autism, taking in mind the relevancy that currently has the same within the global and national organizations, demonstrating the need of to identify and to describe the influence of parenting patterns and the development of a secure attachment as Factor in the support in the development of neurocognitive profile of children diagnosed with autism spectrum disorder. The sample was composed by 4 patients of both genders (female: 2 and male: 2) of Center of Sensory Integration for children with autism and disorder in the Developmen (CISADDE IPS), whose ages range between 1 and 5 years old. Methodology the investigation is framed in the paradigm empirical-analytical, Its approach is from the quantitative approach and is considered a descriptive study, given its purpose. To respond to the proposed objectives, It was the administration of the following instruments: the Father-Son Relationship Inventory (PCRI), The Intervention didactics of characterization of the attachment, the Development Inventory (BATTELLE), the Neuropsychological Maturity Questionnaire (CUMANIN) and Scale of evaluation of the infantile autism (CARS). Satisfactory results were reported, Delimiting the attachment and the patterns of rearing the parents, as support factors During the physical, social and mental development, in accordance with the autism level and other characteristics of family dynamics.